Development and validation of a RP–HPLC method for quantization studies of albendazole suspension dosage forms of Rombendazol - Elena Gabriela Oltean; Nica A. (Medicamentul Veterinar)
An isocratic high-performance liquid chromatography (HPLC) procedure was developed and validated for the quantitative determination of albendazole in suspension of Rombendazole. HPLC separation was carried out by reversed phase chromatography on Kromasil C18 (150 mm x 4.6 mm i.e.; 5 μm particle size), held in thermostat at 25°C. The mobile phase consisted of Methanol/ Distilled water (65/35 v/v), with a flow rate of 1.2 ml/ min and UV detection at 308 nm. In order to validate the method, the following parameters have been investigated - linearity (r2=0.9999), range, precision, accuracy, specificity, limit of detection LOD and limit of quantification LOQ. The described method can be successfully applied for the analysis of the active pharmaceutical compound in suspensions.